Knowledge, causes, and experience of inter-professional conflict and rivalry among healthcare professionals in Nigeria - Elijah N. A. Mohammed (BMC, 2022)
Abstract Introduction The healthcare workforce is regarded as an essential component of any functioning health system, and a lack of optimal collaboration among this group can result to poor quality healthcare services to the population. In Nigerian setting, the health sector is faced with challenges of inter-professional conflict and rivalry. This study aimed at understanding knowledge, causes, and experience of inter-professional conflict and rivalry among healthcare professionals in Nigeria. Methods A cross sectional study was undertaken to administer questionnaires to healthcare personnel in various healthcare facilities in Nigeria. Data were analysed using Statistical Package for Social Sciences. Results A total of 2207 valid responses were received, and male participants were in majority as indicated by 63.7% of the sample. Collectively, doctors and pharmacists represented two-thirds of the sample, and majority of the participants were in the public sector (82.5%). Disparity in salary structure was the highest source of conflict. Whilst almost all the participants indicated that inter-professional rivalry and conflict are prevalent in health sector, about three-quarters of them (73.2%) disagreed that this practice is productive. A considerable number of the respondents had experienced inter-professional conflict and rivalry. Conclusion Evidence from this study can help policymakers in developing framework that can be utilised in addressing rivalry and conflict in the healthcare sector.